MOF Derived High Surface Area Enabled Porous Co3O4 Nanoparticles for Supercapacitors. Issue 27 (22nd July 2019) - Saraf, Mohit; Rajak, Richa; Mobin, Shaikh M.
Abstract: In this work, solvothermally grown ZIF‐67 MOF crystals were utilized as single source molecular precursor, which were transformed into porous Co3 O4 nanoparticles through a simple calcination treatment. The crystal structure of ZIF‐67 was also authenticated by single crystal x‐ray analysis. Further, Co3 O4 nanoparticles were incorporated as supercapacitor electrode. The results show that ZIF‐67 derived Co3 O4 nanoparticles deliver an appreciable specific capacitance (190 F g −1 at 5 A g −1 ) with high capacitance retention (71.42% after 5000 cycles). The comparison with previous state‐of‐the‐arts highlights the importance of MOF derived nanomaterials for achieving superior electrochemical performance. Abstract : ZIF‐67 derived Co3 O4 nanoparticles based electrode is a potential energy storage candidate.